Analisis pengaruh konsumsi, investasi dan tenaga kerja terhadap pertumbuhan ekonomi Provinsi Jambi - Sri Sarmita Dewi; Erfit Erfit; Siti Aminah (Konsentrasi Ekonomi Sumberdaya Alam dan Manusia, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2019)
This research aims to find out how influence from free variable (household consumption, investment and labor) to the dependent variable (economic growth). Hypothesis testing the influence of household consumption, investment,and labor there is a significant relationship to economic growth in the province of jambi, this is adjusted to economic theory that economic growth will be explained by investment then this can be proven by using the F-test (collectively) and t-test (partially) with a 95% confidence level or significance level (α = 0.05). The result from data processing that: 1) The variable of domestic consumption had positive effect and significant to economic growth; 2) The variable of investment has positive effect and significant to economic growth; 3) The variable of labor had positifve effect and significant to economic growth Keywords: Economic Growth, Household Consumption, Investment, Labor.